Vida y pensamiento de un africano excepcional: Amílcar Cabral - Varela Barraza, Hilda (El Colegio de México, 2023)
Fifty years after his assassination, Amílcar Cabral continues to be one of the most influential African thinkers with world-wide recognition. This article proposes a re-reading of this life and thought, highlighting the ways in which he transcended his context (the war against Portuguese colonialism) and his historical moment (the Cold War, at a time when most African countries where fighting against the colonial yoke, or had just achieved their independence). This is not an exhaustive study of a short, yet dense, life and of his prolific thought. Rather, the objective is to highlight some of his most significant experiences which shaped his  revolutionary praxis. This study is centered in the re-reading of the main compendium of his writings (1975). The conclusion is that his assassination was the start of the end for the freedom dreams in Guinea-Bissau, but that his thought is still lighting the way for popular activists, especially outside of Africa.